Randomized Pragmatic Trial of Nasogastric Tube Placement in Patients with Upper Gastrointestinal Tract Bleeding. (April 2017) - Rockey, Don C; Ahn, Chul; de Melo, Silvio W
The value of nasogastric (NG) tube placement in patients with upper gastrointestinal tract bleeding (UGIB) is unclear. We therefore aimed to determine the usefulness of NG tube placement in patients with UGIB. The study was a single-blind, randomized, prospective, non-inferiority study comparing NG placement (with aspiration and lavage) to no NG placement (control). The primary outcome was the probability that physicians could predict the presence of a high-risk lesion (ie, requiring endoscopic therapy). 140 patients in each arm were included; baseline clinical features were similar in each group. The probability that there would be a high-risk lesion in the control arm was predicted to be 35% compared with 39% in the NG arm (after NG placement)—a probability difference of −4% (95% CI −12% to 3%), which confirmed non-inferiority of the 2 arms (p=0.002). All patients underwent endoscopy and all patients with high-risk lesions had endoscopic therapy. Physicians predicted the specific culprit lesion in 38% (53/140) and 39% (55/140) of patients in the control and NG (after NG placement) groups, respectively. The presence of coffee grounds or red blood in the NG aspirate did not change physician assessments. Pain, nasal bleeding, or failure of NG occurred in 47/140 (34%) patients. There were no differences in rebleeding rates or mortality. In patients with acute UGIB, the ability of physicians to predict culprit bleeding lesions and/or the presence of high-risk lesions was poor. Routine NG placement did not improve physician's predictive ability, did not affect outcomes, and was complicated in one-third of patients. Trail Registration Number: NCT00689754.